Lumi Education–Assisted Problem-Based Mathematics Modules to Foster Students’ Mathematical Problem-Solving and Scientific Reasoning - Erlan Juarsa; Elita Zusti Jamaan (Postgraduate, University of Mataram, 2026)
This research aimed to develop mathematics teaching modules based on Problem-Based Learning (PBL) with Lumi Education assistance to enhance students' mathematical problem-solving abilities. The development research employed the Plomp model, consisting of preliminary investigation, prototyping, and assessment phases. Data collection utilized interviews, questionnaires, checklists, and mathematical problem-solving ability tests. The resulting teaching module and student worksheets demonstrated excellent validity with validity scores of 3.64 and 3.62, respectively, across content feasibility, presentation, graphic, and language aspects. Practicality assessment revealed 91% student response during small group evaluation and 85.36% during field testing, both rated as highly practical. Additionally, educator responses reached 93% practicality rating. The module proved effective with an average percentage of 71.87% in enhancing students' mathematical problem-solving abilities. This research concludes that the PBL-based teaching module assisted by Lumi Education for matrix material is valid, practical, and effective for improving mathematical problem-solving skills among vocational high school students.